Evaluating NIRS for predicting faecal fibre, protein fractions and digestibility in dairy sheep and goats fed alfalfa hay and concentrate - M. Simoni; T. Danese; A. Guerra; A. Goi; R. Pitino; M. De Marchi; C. Mitsiopoulou; P. Kyriakaki; A. Mavrommatis; E. Tsiplakou; F. Righi (Italian Journal of Animal Science)
This study evaluated the effectiveness of near-infrared spectroscopy (NIRS) in predicting faecal fibre, protein fractions and total tract apparent digestibility in dairy sheep and goats fed varying ratios of alfalfa-hay and concentrate. A total of 180 faecal samples from dairy sheep and goats were collected and chemically analysed. Faecal samples underwent also NIRS spectral acquisition and calibration models were obtained through modified partial least square regression and tested for robustness. The NIRS provided excellent estimations for N and CP as % as is (R2ExV 0.91 and 0.91, RPD 3.16 and 3.33, respectively), good estimation for N, CP and ND soluble CP % DM (R2ExV 0.90, 0.90 and 0.85, RPD 3.14, 2.90 and 2.48) and ND soluble CP expressed as % as is (R2ExV 0.87, RPD 2.55), approximative quantitative prediction for acid detergent insoluble crude protein (ADICP) and ADIN % acid detergent fibre (ADF) (R2ExV 0.79 and 0.71, RPD 1.93 and 1.78, respectively) and ADICP as % as is (R2ExV 0.67, RPD 1.70) but resulted to be less effective when predicting all the other components. The prediction models for total-tract digestibility (ttD) of ADICP performed best among the developed equations (R2ExV 0.57, RPD 1.38), but the model was not sufficient for precise predictions, suggesting a good capacity of NIRS to predict faecal N excretion but also intrinsic limitations of faecal spectra due to the partial residual nutrients content, compared to the diet. Increasing the number of calibration samples and values, the forage species, and the F:C ratios in the diet offered to the animals could improve the NIRS performance.